2009
DOI: 10.1002/jso.21243
|View full text |Cite
|
Sign up to set email alerts
|

The relation between hypoxia‐inducible factor (HIF)‐1alpha expression with p53 expression and outcome in surgically treated supraglottic laryngeal cancer

Abstract: The data suggest that HIF-1alpha expression does not have a prognostic value in surgically treated supraglottic laryngeal SCC, and that immunohistochemical determination of p53 does not allow improving the clinical significance of HIF-1alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…HIF-1α and GLUT-1 are the intrinsic hypoxia markers that have been studied the most in various tumours (13)(14)(15)(16)(17)(18). Nevertheless, few studies have investigated the value of HIF-1α (22,23,28,29) or GLUT-1 expression (24,25) alone for the prediction of clinical outcome and survival rate of laryngeal carcinoma and, to the best of our knowledge, there is …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIF-1α and GLUT-1 are the intrinsic hypoxia markers that have been studied the most in various tumours (13)(14)(15)(16)(17)(18). Nevertheless, few studies have investigated the value of HIF-1α (22,23,28,29) or GLUT-1 expression (24,25) alone for the prediction of clinical outcome and survival rate of laryngeal carcinoma and, to the best of our knowledge, there is …”
Section: Discussionmentioning
confidence: 99%
“…Wildeman et al suggested that the effect of hypoxia-related proteins, including carbonic anhydrase IX and HIF-1α, on an increased risk for local recurrence of laryngeal carcinoma is stronger following radiotherapy (29). Cabanillas et al reported a significant positive correlation between HIF-1α and T classification, but no association was observed with other clinicopathological variables or with the prognosis of supraglottic laryngeal squamous cell carcinoma (28). Although HIF-1α expression was significantly associated with a poorer survival rate in a univariate model in the present study, multivariate analysis revealed no significant association.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following a review of the literature, only 13 studies on the topic of laryngeal carcinoma and HIF were identified (Table I). These studies all examined the expression of HIF-1α only, and none investigated HIF-1α mRNA expression levels from in vivo samples (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The current study is the first to present full quantitative data regarding the mRNA expression levels of HIF-1α and HIF-2α in laryngeal carcinoma samples, and is the first to report on the mRNA expression levels of HIF-3α in an in vivo study of a malignant neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on whether HIF-1α expression in human laryngeal carcinoma tissue is associated with tumor progression and lymph node metastasis. However, those conclusions have been inconsistent thus far (11,12). …”
Section: Introductionmentioning
confidence: 95%